Exploration of Pricing Strategies in North Cyprus Hotels - Falalieiev, Anatolia (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: The purpose of this study is to explore pricing strategies in the hotel industry. The importance of pricing and price setting in relation to profit maximization objectives of businesses is well known. Understanding the processes of pricing, factors influencing pricing decisions, and strategies developed in the businesses are the key issues this study aims to find out. The study will be carried out in the hospitality businesses where literature related to hotels and their pricing is widely covered. The study’s primary data collection is done in the 4 and 5 star hotels of North Cyprus. The importance of tourism on economic and social development of North Cyprus is a known fact. Resort hotels with different facilities and services are being built and marketed in the last few years. Therefore, understanding their concept and their pricing practices is believed to yield valuable information. Four and five star hotels together with holiday villages are included in the data collection. Sales/marketing managers, accounting/finance managers and/or general managers were the respondents. One manager from each hotel is accessed and in total 18 interviews were carried out. The outcomes of these interviews were initially transcribed and then analyzed by using qualitative data categorizations. The results of the present study revealed that four and five star hotels and holiday villages of Northern Cyprus are utilizing different types of pricing strategies. A precondition for such decisions is the influence of external and internal factors while selecting appropriate pricing strategy. The key external factors are determined to be seasonality, location, competition and demand fluctuation; whereas main type of the internal factors is the service quality and costs. Appropriate price setting are based on review of previous data, occupancy level and average room rate (ARR). As a result of the interviews with the hotel managers, price fairness depends on the quality of the hotel and satisfaction and happiness of the customers. Generally, managers conduct surveys and review comments on the website for assessing the quality of services provided to customers during their stay in the hotel. In the financial evaluation process, the managers stated that their main concern is the fixed and variable costs, together with the timely examination of marginal cost and revenue in their aim to maximize profitability. Keywords: pricing, pricing policy, pricing strategies, hotels, North Cyprus ………………………………………………………………………………………………………………………… ÖZ: Bu çalışmanın amacı otellerdeki fiyat stratejilerinin araştırılmasıdır. Fiyat ve fiyatlandırma yöntemlerinin işletmelerin azami karlılık hedeflerine ulaşmadaki önemi bilinen bir gerçektir. Dolayısı ile, bu çalışmadaki ana tema fiyatlandırma süreci, fiyatlandırma kararını etkileyen faktörler ve kullanılan stratejilerdir. Kuzey Kıbrıs turizminin ekonomiye ve sosyal gelişime olan etkisi bilindiğinden, çalışma Kuzey Kıbrıs otel sektörünün dört ve beş yıldızlı otellerini kapsamaktadır. Çalışma pazarlama/satış müdürü, muhasebe/finans müdürü, ve/veya genel müdür ile yapılan mülakatlar ile yürütüldü. Her otelden tek müdür olmak üzere toplam 18 mülakat yapıldı. Sonuçlar dört ve beş yıldızlı otellerin farklı fiyatlandırma stratejileri kullandığını gösterdi. Bunu yaratan temelde iç ve dış faktörlerin olduğu tespit edildi. Sezonluk talep ve talep dalgalanmaları, yerleşim yeri ve rekabet başlıca öne çıkan dış etkenlerdi. Servis kalitesi ve maliyet ise fiyatlandırmayı etkileyen temel iç faktörlerdir. Yöneticiler doğru fiyatlandırma yapabilmek için çoğunlukla önceki dönemlere ait verileri, doluluk bilgilerini ve ortalama oda fiyatı rakamlarını kullanmaktadır. Sonuçta, otel müdürleri algılanan fiyat adaletinin otelin servis kalitesi ve dolayısı ile müşteri memnuniyetine bağlı olduğunu belirtmiştir. Genellikle müdürler, müşterilerin geri bildirimini ve bazı internet sitelerinin müşteri görüşlerini kullanarak fiyat algılamasını ölçerler. Finansal konularda ise otel müdürleri sabit ve değişken maliyetleri, marjinal maliyet ve gelir ilişkisini kullanırlar. Anahtar kelimeler: fiyatlandırma, fiyatlandırma politikaları, fiyatlandırma stratejileri, oteller, Kuzey Kıbrıs.
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2014. Supervisor: Assist. Prof. Dr. Mine Haktanır.
Keywords: Tourism; Hotel management - Marketing - Hotels - Cyprus, North; Hospitality Industry - Cyprus, North; Pricing, Pricing Policy, Pricing Strategies, Hotels, North Cyprus